Faktor-Faktor yang Mempengaruhi Kinerja Keuangan Pemerintah Daerah Kabupaten/Kota di Jawa Timur - asri nurhamidah; Yuli Chomsatu Samrotun (Jurnal Akuntansi dan Bisnis Syariah, 2025)
This study aims to explore and analyze the influence of Local Original Income (PAD) and capitalexpenditure on the financial performance ofthe Regional Government in Regencies/Cities in EastJava Province for the period 2023. This study uses a quantitative method, with secondary data.The population and sample in this study were 29 Regencies and 9 Cities in the East Java Province. The data collected was the Realization of the 2023 Fiscal Year APBD taken from the websitekemenkeu.go.id. Then the data was processed using the SPSS 25 application and analyzed througha multiple linear regression model. The results of this study indicate that Local Original Income(PAD) statistically has an effect on the financial performance of the Regional Government. WhileCapital Expenditure does not affect the financial performance of the Regional Government. Thisfinding reflects the fairness in the structure of regional financial management, where strengtheningthe capacity of Local Original Income has been proven to be a determinant of the financialperformance of the regional government. Meanwhile, Capital Expenditure will be one of thedeterminants that influences regional financial performance, if used on target so that it can produceassets that can support a region to increase its Local Original Income. However, if CapitalExpenditure cannot be utilized optimally, then Capital Expenditure will not affect FinancialPerformance. Keywords : Influence; Capital Expendicture; Local Original Income; Financial Performance; Local Government